Correlating Self-Report and Trace Data Measures of Incivility: A Proof of Concept. (October 2020) - Hopp, Toby; Vargo, Chris J.; Dixon, Lucas; Thain, Nithum
This study correlated self-report and trace data measures of political incivility. Specifically, we asked respondents to provide estimates of the degree to which they engage in uncivil political communication online. These estimates were then compared to computational measures of uncivil social media discussion behavior. The results indicated that those who self-disclose uncivil online behavior also tend to generate content on social media that is uncivil as identified by Google's Perspective application programming interface. Taken as a whole, this work suggests that combining self-report and behavioral trace data may be a fruitful means of developing multimethod measures of complex communication behaviors.